Sound adsorption and morphological properties of SIS/HIPS/CaCO 3 polymer composites - (:unkn) unknown (My University, 2011)
Characterization of sound-absorbing materials, like mineral wool or polymer foam, in the context of building or transport applications, requires the evaluation of their acoustic and nonacoustic properties. The acoustic properties quantify the material's sound absorbing efficiency, whereas the non-acoustic properties allow one to predict the material's acoustic performance in various industrial applications by the application of the appropriate acoustical model. A sound absorption material composed of blends of styrene isoprene styrene (SIS) rubber and high impact polystyrene (HIPS) has been developed. Its sound absorbing characteristics were investigated in an impedance tube, according to transfer function method. Measurements show that SIS ratios have a significant effect on the acoustic absorption performance of the blend due to their microstructures and physical features. The structure and properties of the blend is characterized using scanning electron microscopy (SEM). Furthermore, a polymer blend of styrene isoprene styrene rubber and high impact polystyrene was tested in order to quantify its hardness and Izod impact strength properties. © MD Publications Pvt. Ltd.
Keywords: High impact polystyrene; Impedance ratio; Insulation; Polymer blends; Sound absorption; Styrene isoprene styrene; Thermoplastic elastomer